Warum werden Autoren vergessen?: Mechanismen literarischer Kanonisierung am Beispiel von Paul Heyse und Wilhelm Raabe - Grube, Christoph (transcript, 2014)
Not literary quality decides whether a text and its author enter the collective memory, but complex mechanisms do, and for the first time these are completely shown in this study based on empirical results.